Cronobacter sakazakii and Microbiological Parameters in Dairy Formulas Associated With a Food Alert in Chile - Parra-Flores, Julio; Cerda-Leal, Fabiola; Contreras, Alejandra; Valenzuela-Riffo, Nicole; Rodríguez, Alejandra; Aguirre, Juan (Frontiers in Microbiology, 2018)
The objective of this study was to evaluate the presence of Cronobacter sakazakii and microbiological parameters in dairy products associated with athe food alert. Ninety dairy product samples were analyzed, including seven commercial brands and two product types (liquid and powdered) from four countries. Aerobic plate count and Enterobacteriaceae count were performed according to Chilean standards. Cronobacter spp. and Cronobacter sakazakii were identified by polymerase chain reaction real time amplification of rpoB and cgcA genes and the genotype by multilocus sequence typing. Eighty-eight percent Aerobic plate count was positive in 88% of dairy products showed aerobic plate count higher than the detection limit. Fifty percent of liquid commercial brand samples contained aerobic plate count: 2.6 CFUUFC/mL, 2.3 CFUUFC/mL, 1.1 CFUUFC/mL, and 2.9 CFUUFC/mL in brands A, C, E, and G, respectively. Results for powdered commercial brands were 3.0 CFUUFC/g, 3.6 CFUUFC/g, and 5.7 CFUUFC/g in brands B, D, and F, respectively. Maximum count (5.7 CFUUFC/g) occurred in brand F dairy product manufactured in Chile. Enterobacteriaceae were found in 55% of the samples, 64% in liquid and 51% in powdered commercial brands. In 50% of brands B, D, and E, samples contained 2.9, 2.8, and 2.7 log CFUUFC/g, respectively. Only liquid commercial brands from the United States had Enterobacteriaceae values between 0.10 and 4.54 CFUUFC/mL. Seventeen suspicious strains were isolated and nine were identified as Enterobacter spp. Only eight suspicious strains from four powdered commercial brands (Chile and Singapore) were confirmed as Cronobacter sakazakii by rpoB and cgcA gene amplification and fusA sequencing. Cronobacter sakazakii prevalence in the analyzed samples was 8.8%. There were 11% of powdered milk brands that contained aerobic plate count between 4.0 and 4.7 log CFU/g and 55% of the samples contained Enterobacteriaceae. Cronobacter sakazakii was found in dairy products manufactured in Chile and Singapore. On the basis of this information, the Chilean Ministry of Health (RSA) decreed a national and international food alert and recalled all the product batches that resultedtested positive in the present study from supermarkets and pharmacies.